PENGARUH KURS SPOT DAN KURS FORWARD DALAM MEMPREDIKSI FUTURE SPOT PADA PASAR VALAS KAWASAN ASIA TENGGARA - I Gusti Ayu Kade Diana Yanthi; Luh Gede Sri Artini (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2013)
The importance of the activity in foreign exchange occur as the result of the development of international trading and increased international money and capital movement. The vast development of international economic  caused  economic relationship  among  countries  will  be  linked  to  each other  and  subsequently improve trading activities in their goods, money and capital flows. The variables used in this study are spot, forward  and future  spot. Based  on  the result  of Regression  Estimation  applied in  hypothesis on foreign currencies exchange which done simultaneously are proven able to predict future spot. The investor and international economic  actor could use spot  exchange rate and forward  exchange rate as a  short terms predictor for the next trimester in 2011.